Lightweight thermal-insulation high-strength building material and preparation method thereof

By using silicate cement, light aggregate, mineral fiber and modified nanosilicon dioxide, plant fiber and microcapsule phase change materials in building materials, the problems of large weight and poor insulation properties of traditional building materials are solved. It has achieved lightweight, efficient thermal insulation and environmental protection, forming a new type of material suitable for green buildings.

CN119263739AInactive Publication Date: 2025-01-07HAINAN DEYINGMAN IND CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411542999.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-01-07
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing lightweight and thermal insulation high-strength building materials have shortcomings in performance and environmental protection. Traditional materials have large weight and poor thermal insulation performance. New materials require a large amount of chemical additives during the preparation process, resulting in high costs and environmental pollution.

Method used

Silicate cement, light aggregate and mineral fiber are used as the main components, combined with modified nanosilicon dioxide, plant fiber and microcapsule phase change materials as additives, and through optimized proportion and preparation process, lightweight insulation and high strength are formed. Building materials ensure the lightweight, efficient insulation and environmental protection of the materials.

Benefits of technology

It realizes the lightweight and high-strength coexistence of materials, has excellent thermal insulation performance and environmental protection characteristics, reduces energy consumption and environmental pollution, and is in line with the concept of green building.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119263739A_ABST
    Figure CN119263739A_ABST
Patent Text Reader

Abstract

The invention discloses a lightweight thermal-insulation high-strength building material and a preparation method thereof, the building material takes Portland cement, lightweight aggregate and mineral fiber as main components, and modified nano silicon dioxide, a plant fiber reinforcing agent and a microcapsule phase change material are added as additives. The modified nano silicon dioxide is prepared through a specific process, the plant fiber reinforcing agent is prepared from bamboo fibers, linen fibers and polyvinyl chloride powder, and the microcapsule phase change material has the phase change temperature of 28-45 DEG C. In the material preparation process, the main components and the modified nano silicon dioxide are mixed firstly, then the plant fiber reinforcing agent is subjected to pre-wetting treatment, the microcapsule phase change material and a proper amount of water are added, then stirring forming is conducted, and finally curing, curing and post-treatment are conducted. The building material has the characteristics of light weight, heat preservation, high strength and the like, and is suitable for construction of environment-friendly heat-preservation buildings. The preparation method disclosed by the invention is simple and feasible, can be used for large-scale production, and provides a new idea for innovation of building materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of environmentally friendly building materials, and specifically discloses a lightweight, heat-insulating, high-strength building material and a preparation method thereof. Background Art

[0002] In the construction industry, with the increasing requirements for energy conservation and environmental protection, the demand for lightweight, heat-insulating and high-strength building materials is growing. Traditional building materials, such as ordinary concrete and bricks, although they have high strength, often have defects such as heavy weight and poor heat preservation performance, which can hardly meet the needs of modern buildings for lightweight and high-efficiency heat preservation.

[0003] In recent years, some new building materials, such as aerated concrete and foamed concrete, have achieved lightweight to a certain extent, but their thermal insulation performance and strength still need to be improved. In addition, these materials often require a large amount of chemical additives during the preparation process, which not only increases costs but also may cause environmental pollution.

[0004] In order to overcome the shortcomings of existing technologies, some researchers have begun to explore the introduction of natural materials such as nanomaterials and plant fibers into building materials to improve their thermal insulation and strength. However, these attempts often have some problems. For example, the poor dispersion of nanomaterials in building materials can easily lead to uneven material properties; the addition of plant fibers may reduce the overall strength of the material, and its weather resistance and durability also need to be verified.

[0005] Therefore, there are still many deficiencies in the lightweight, thermal-insulating, and high-strength building materials in the prior art. A new type of building material is needed that can be lightweight, highly efficient in thermal insulation, and have sufficient strength, while also having a simple preparation process, low cost, and is environmentally friendly and pollution-free. Summary of the invention

[0006] In view of the deficiencies in the prior art, the present invention provides a lightweight, heat-insulating, high-strength building material and a preparation method thereof.

[0007] The present invention includes the following technical solutions:

[0008] A lightweight, heat-insulating, high-strength building material, comprising silicate cement, lightweight aggregate and mineral fiber as main components, and comprising modified nano silicon dioxide, plant fiber reinforcement and microcapsule phase change material as additive components; the modified nano silicon dioxide is added in an amount of 1.5-2.5wt%, the plant fiber reinforcement is added in an amount of 3-5wt%, and the microcapsule phase change material is added in an amount of 4-6wt%.

[0009] The above-mentioned lightweight heat-insulating high-strength building material, the modified nano-silicon dioxide is prepared by the following steps:

[0010] 1) Place the nano-silicon dioxide powder in an oven and dry it at 100-120°C for 12-24 hours to remove moisture and impurities adsorbed on the surface;

[0011] 2) dispersing the dried nano-silicon dioxide powder in anhydrous ethanol, and forming a uniform dispersion by ultrasonic treatment or high-speed stirring, wherein the content of the nano-silicon dioxide powder is 10-20wt%;

[0012] 3) mixing sodium lauryl sulfate and alumina powder with propylene glycol to form a modified solution, wherein the content of sodium lauryl sulfate is 5-10wt%, and the content of alumina powder is 2-5wt%;

[0013] 4) slowly adding the above modifier solution to the nano-silicon dioxide dispersion at a volume ratio of 1:5-10; while keeping stirring, so that the modifier is evenly covered on the surface of the nano-silicon dioxide by adsorption or coating;

[0014] 5) removing excess solvent and unabsorbed modifier by centrifugation, filtration or evaporation, and obtaining modified nano-silicon dioxide powder with a water content of less than 8 wt % after drying.

[0015] Furthermore, in the above-mentioned lightweight heat-insulating high-strength building material, the plant fiber reinforcing agent includes bamboo fiber and flax fiber, and is made by the following steps:

[0016] 1) Pretreatment: The bamboo fiber and flax fiber are pretreated separately, including washing, drying, and bleaching steps to remove surface impurities and grease, and the fibers are crushed into fragments less than 5 mm in length;

[0017] 2) Mixing: In a mixer, 10 parts of bamboo fiber, 3-6 parts of flax fiber and 5-10 parts of polyvinyl chloride powder are uniformly mixed by weight;

[0018] 3) Extrusion: The mixed materials are fed into a twin-screw extruder for extrusion, with the feeding zone at 50-60°C, the preheating zone at 100-110°C, the melting zone at 150-170°C, and the mixing zone at 175-185°C;

[0019] 4) Cooling and grinding: Cooling and grinding after extrusion, passing through a 50-mesh sieve to obtain the plant fiber reinforcing agent.

[0020] Furthermore, in the above-mentioned lightweight thermal insulation and high-strength building material, the microcapsule phase change material is a microcapsule phase change material with a phase change temperature of 28-45°C.

[0021] Furthermore, the above-mentioned lightweight, thermal-insulating, high-strength building material is made of the following materials, calculated by mass percentage: 30-40.0wt% of silicate cement, 20-30.0wt% of lightweight aggregate, 25-35wt% of mineral fiber, 1.5-2.5wt% of modified nano-silicon dioxide, 3.0-5.0wt% of plant fiber reinforcement, and 4.0-6.0wt% of microcapsule phase change material.

[0022] Furthermore, the above-mentioned lightweight, thermal-insulating, high-strength building material is made of the following materials, calculated by mass percentage: 35.0wt% of silicate cement, 25.0wt% of lightweight aggregate, 29wt% of mineral fiber, 2.0wt% of modified nano-silicon dioxide, 4.0wt% of plant fiber reinforcement, and 5.0wt% of microcapsule phase change material.

[0023] The invention discloses application of the lightweight heat-insulating high-strength building material in the construction of environmentally friendly heat-insulating buildings.

[0024] Furthermore, the present invention discloses a method for preparing the above-mentioned lightweight thermal insulation high-strength building material, comprising the following steps:

[0025] S1 Mixing stage: Mix the silicate cement, lightweight aggregate, mineral fiber and modified nano-silicon dioxide in proportion to ensure that each component is fully dispersed;

[0026] S2 Pre-wetting treatment: Add appropriate amount of water to the plant fiber reinforcement for pre-wetting treatment to improve its dispersibility and binding force in the mixture;

[0027] S3 stirring and molding: adding the microcapsule phase change material and the pre-wetted plant fiber to the mixture obtained in step S1, adding an appropriate amount of water to adjust to a suitable workability, stirring mechanically until uniform, and molding using a mold;

[0028] S4 Curing and solidification: The formed materials are cured for 7-10 days under standard curing conditions at a temperature of 20±2℃ and a relative humidity of ≥90% to allow the cement to fully hydrate and harden, while the microcapsule phase change material is evenly distributed and fixed inside the material;

[0029] S5 post-processing: According to the needs, the finished product is cut, polished and processed to finally obtain lightweight, thermal insulation and high-strength building materials.

[0030] Furthermore, in the above preparation method, in S2, the mass ratio of the plant fiber reinforcing agent to water is 1:1-2; and in S3, the mass ratio of the building material to water is 1:0.2-0.4.

[0031] Compared with the prior art, the present invention has the following beneficial effects:

[0032] The invention discloses a light-weight heat-insulating high-strength building material and a preparation method thereof.

[0033] First of all, this building material achieves the characteristics of both lightness and high strength by optimizing the proportion and introducing special additives. Compared with traditional building materials, it greatly reduces the weight of the building, which is conducive to reducing the difficulty of foundation treatment and structural design, while maintaining excellent mechanical properties, ensuring the safety and stability of the building.

[0034] Secondly, the material has excellent thermal insulation performance. The addition of microcapsule phase change materials enables building materials to automatically adjust the indoor temperature within a certain temperature range, effectively reducing energy consumption and improving energy efficiency. This not only conforms to the current green and environmentally friendly building concept, but also provides users with a more comfortable living environment.

[0035] In addition, the modified nano-silica and plant fiber reinforcement used in the preparation process not only improve the overall performance of the material, but also give it good environmental protection characteristics. The use of these additives reduces the emission of harmful substances, reduces pollution to the environment, and meets the requirements of sustainable development. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 Comparison of compressive strength (Mpa) between Examples 1-3 and Comparative Examples 1-5;

[0037] Figure 2 Comparison of flexural strength (Mpa) between Examples 1-3 and Comparative Examples 1-5;

[0038] Figure 3 The density (kg / m 3 )

[0039] Figure 4 Comparison of thermal insulation performance tests between Examples 1-3 and Comparative Examples 1-5. DETAILED DESCRIPTION

[0040] A lightweight, heat-insulating, high-strength building material, which is made of the following materials, calculated by mass percentage: 30-40.0wt% of silicate cement, 20-30.0wt% of lightweight aggregate, 25-35wt% of mineral fiber, 1.5-2.5wt% of modified nano-silicon dioxide, 3.0-5.0wt% of plant fiber reinforcing agent, and 4.0-6.0wt% of microcapsule phase change material;

[0041] The modified nano silicon dioxide is prepared by the following steps:

[0042] 1) Place the nano-silicon dioxide powder in an oven and dry it at 100-120°C for 12-24 hours to remove moisture and impurities adsorbed on the surface;

[0043] 2) dispersing the dried nano-silicon dioxide powder in anhydrous ethanol, and forming a uniform dispersion by ultrasonic treatment or high-speed stirring, wherein the content of the nano-silicon dioxide powder is 10-20wt%;

[0044] 3) mixing sodium lauryl sulfate and alumina powder with propylene glycol to form a modified solution, wherein the content of sodium lauryl sulfate is 5-10wt%, and the content of alumina powder is 2-5wt%;

[0045] 4) slowly adding the above modifier solution to the nano-silicon dioxide dispersion at a volume ratio of 1:5-10; while keeping stirring, so that the modifier is evenly covered on the surface of the nano-silicon dioxide by adsorption or coating;

[0046] 5) removing excess solvent and unabsorbed modifier by centrifugation, filtration or evaporation, and obtaining modified nano-silicon dioxide powder with a water content of less than 8 wt % after drying.

[0047] The plant fiber reinforcing agent includes bamboo fiber and flax fiber and is prepared by the following steps:

[0048] 1) Pretreatment: The bamboo fiber and flax fiber are pretreated separately, including washing, drying, and bleaching steps to remove surface impurities and grease, and the fibers are crushed into fragments less than 5 mm in length;

[0049] 2) Mixing: In a mixer, 10 parts of bamboo fiber, 3-6 parts of flax fiber and 5-10 parts of polyvinyl chloride powder are uniformly mixed by weight;

[0050] 3) Extrusion: The mixed materials are fed into a twin-screw extruder for extrusion, with the feeding zone at 50-60°C, the preheating zone at 100-110°C, the melting zone at 150-170°C, and the mixing zone at 175-185°C;

[0051] 4) Cooling and grinding: Cooling and grinding after extrusion, passing through a 50-mesh sieve to obtain the plant fiber reinforcing agent.

[0052] The method for preparing the above-mentioned lightweight thermal insulation high-strength building material is characterized by comprising the following steps:

[0053] S1 Mixing stage: Mix the silicate cement, lightweight aggregate, mineral fiber and modified nano-silicon dioxide in proportion to ensure that each component is fully dispersed;

[0054] S2 Pre-wetting treatment: Add appropriate amount of water to the plant fiber reinforcement for pre-wetting treatment to improve its dispersibility and binding force in the mixture;

[0055] S3 stirring and molding: adding the microcapsule phase change material and the pre-wetted plant fiber to the mixture obtained in step S1, adding an appropriate amount of water to adjust to a suitable workability, stirring mechanically until uniform, and molding using a mold;

[0056] S4 Curing and solidification: The formed materials are cured for 7-10 days under standard curing conditions at a temperature of 20±2℃ and a relative humidity of ≥90% to allow the cement to fully hydrate and harden, while the microcapsule phase change material is evenly distributed and fixed inside the material;

[0057] S5 post-processing: According to the needs, the finished product is cut, polished and processed to finally obtain lightweight, thermal insulation and high-strength building materials.

[0058] In S2, the mass ratio of the plant fiber reinforcing agent to water is 1:1-2; in S3, the mass ratio of the building material to water is 1:0.2-0.4.

[0059] The microcapsule phase change material is 28°C PCM phase change material (Thermalcare PCM28°C, Shanghai Xinya New Material Technology Co., Ltd.).

[0060] The silicate cement is 425 grade silicate cement.

[0061] Lightweight aggregate is 3-6mm expanded vermiculite purchased from Lingshou County Pengxian Mineral Products Processing Plant

[0062] Mineral fiber is basalt fiber purchased from Taian Hongfa New Materials Co., Ltd.

[0063] Nano-silicon dioxide, average particle size 200nm.

[0064] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0065] Example 1

[0066] A lightweight, heat-insulating, high-strength building material, which is made of the following materials, calculated by mass percentage: 30wt% of silicate cement, 30.0wt% of lightweight aggregate, 31.5wt% of mineral fiber, 1.5wt% of modified nano-silicon dioxide, 3.0wt% of plant fiber reinforcing agent, and 4.0wt% of microcapsule phase change material;

[0067] The modified nano silicon dioxide is prepared by the following steps:

[0068] 1) Place the nano-silicon dioxide powder in an oven and dry it at 100-120°C for 12-24 hours to remove moisture and impurities adsorbed on the surface;

[0069] 2) dispersing the dried nano-silicon dioxide powder in anhydrous ethanol, and forming a uniform dispersion by ultrasonic treatment or high-speed stirring, wherein the content of the nano-silicon dioxide powder is 15wt%;

[0070] 3) mixing sodium lauryl sulfate and alumina powder with propylene glycol to form a modified solution, wherein the content of sodium lauryl sulfate is 7.5wt% and the content of alumina powder is 3.5wt%;

[0071] 4) slowly adding the above modifier solution to the nano-silicon dioxide dispersion at a volume ratio of 1:8; while maintaining stirring, so that the modifier is evenly covered on the surface of the nano-silicon dioxide by adsorption or coating;

[0072] 5) removing excess solvent and unabsorbed modifier by centrifugation, filtration or evaporation, and obtaining modified nano-silicon dioxide powder with a water content of less than 8 wt % after drying.

[0073] The plant fiber reinforcing agent includes bamboo fiber and flax fiber and is prepared by the following steps:

[0074] 1) Pretreatment: The bamboo fiber and flax fiber are pretreated separately, including washing, drying, and bleaching steps to remove surface impurities and grease, and the fibers are crushed into fragments less than 5 mm in length;

[0075] 2) Mixing: In a mixer, 10 parts of bamboo fiber, 4.5 parts of flax fiber and 7.5 parts of polyvinyl chloride powder are uniformly mixed by weight;

[0076] 3) Extrusion: The mixed materials are fed into a twin-screw extruder for extrusion, with the feeding zone at 50-60°C, the preheating zone at 100-110°C, the melting zone at 150-170°C, and the mixing zone at 175-185°C;

[0077] 4) Cooling and grinding: Cooling and grinding after extrusion, passing through a 50-mesh sieve to obtain the plant fiber reinforcing agent.

[0078] The method for preparing the above-mentioned lightweight thermal insulation high-strength building material is characterized by comprising the following steps:

[0079] S1 Mixing stage: Mix the silicate cement, lightweight aggregate, mineral fiber and modified nano-silicon dioxide in proportion to ensure that each component is fully dispersed;

[0080] S2 Pre-wetting treatment: Add appropriate amount of water to the plant fiber reinforcement for pre-wetting treatment to improve its dispersibility and binding force in the mixture;

[0081] S3 stirring and molding: adding the microcapsule phase change material and the pre-wetted plant fiber to the mixture obtained in step S1, adding an appropriate amount of water to adjust to a suitable workability, stirring mechanically until uniform, and molding using a mold;

[0082] S4 Curing and solidification: The formed materials are cured for 7-10 days under standard curing conditions at a temperature of 20±2℃ and a relative humidity of ≥90% to allow the cement to fully hydrate and harden, while the microcapsule phase change material is evenly distributed and fixed inside the material;

[0083] S5 post-processing: According to the needs, the finished product is cut, polished and processed to finally obtain lightweight, thermal insulation and high-strength building materials.

[0084] In S2, the mass ratio of the plant fiber reinforcing agent to water is 1:1.5; in S3, the mass ratio of the building material to water is 1:0.3.

[0085] The microcapsule phase change material is 28°C PCM phase change material (Thermalcare PCM28°C, Shanghai Xinya New Material Technology Co., Ltd.).

[0086] Example 2

[0087] A lightweight, heat-insulating, high-strength building material, which is made of the following materials, calculated by mass percentage: 35.0wt% of silicate cement, 25.0wt% of lightweight aggregate, 29wt% of mineral fiber, 2.0wt% of modified nano-silicon dioxide, 4.0wt% of plant fiber reinforcing agent, and 5.0wt% of microcapsule phase change material;

[0088] The modified nano silicon dioxide is prepared by the following steps:

[0089] 1) Place the nano-silicon dioxide powder in an oven and dry it at 100-120°C for 12-24 hours to remove moisture and impurities adsorbed on the surface;

[0090] 2) dispersing the dried nano-silicon dioxide powder in anhydrous ethanol, and forming a uniform dispersion by ultrasonic treatment or high-speed stirring, wherein the content of the nano-silicon dioxide powder is 15wt%;

[0091] 3) mixing sodium lauryl sulfate and alumina powder with propylene glycol to form a modified solution, wherein the content of sodium lauryl sulfate is 7.5wt% and the content of alumina powder is 3.5wt%;

[0092] 4) slowly adding the above modifier solution to the nano-silicon dioxide dispersion at a volume ratio of 1:8; while maintaining stirring, so that the modifier is evenly covered on the surface of the nano-silicon dioxide by adsorption or coating;

[0093] 5) removing excess solvent and unabsorbed modifier by centrifugation, filtration or evaporation, and obtaining modified nano-silicon dioxide powder with a water content of less than 8 wt % after drying.

[0094] The plant fiber reinforcing agent includes bamboo fiber and flax fiber and is prepared by the following steps:

[0095] 1) Pretreatment: The bamboo fiber and flax fiber are pretreated separately, including washing, drying, and bleaching steps to remove surface impurities and grease, and the fibers are crushed into fragments less than 5 mm in length;

[0096] 2) Mixing: In a mixer, 10 parts of bamboo fiber, 4.5 parts of flax fiber and 7.5 parts of polyvinyl chloride powder are uniformly mixed by weight;

[0097] 3) Extrusion: The mixed materials are fed into a twin-screw extruder for extrusion, with the feeding zone at 50-60°C, the preheating zone at 100-110°C, the melting zone at 150-170°C, and the mixing zone at 175-185°C;

[0098] 4) Cooling and grinding: Cooling and grinding after extrusion, passing through a 50-mesh sieve to obtain the plant fiber reinforcing agent.

[0099] The method for preparing the above-mentioned lightweight thermal insulation high-strength building material is characterized by comprising the following steps:

[0100] S1 Mixing stage: Mix the silicate cement, lightweight aggregate, mineral fiber and modified nano-silicon dioxide in proportion to ensure that each component is fully dispersed;

[0101] S2 Pre-wetting treatment: Add appropriate amount of water to the plant fiber reinforcement for pre-wetting treatment to improve its dispersibility and binding force in the mixture;

[0102] S3 stirring and molding: adding the microcapsule phase change material and the pre-wetted plant fiber to the mixture obtained in step S1, adding an appropriate amount of water to adjust to a suitable workability, stirring mechanically until uniform, and molding using a mold;

[0103] S4 Curing and solidification: The formed materials are cured for 7-10 days under standard curing conditions at a temperature of 20±2℃ and a relative humidity of ≥90% to allow the cement to fully hydrate and harden, while the microcapsule phase change material is evenly distributed and fixed inside the material;

[0104] S5 post-processing: According to the needs, the finished product is cut, polished and processed to finally obtain lightweight, thermal insulation and high-strength building materials.

[0105] In S2, the mass ratio of the plant fiber reinforcing agent to water is 1:1.5; in S3, the mass ratio of the building material to water is 1:0.3.

[0106] The microcapsule phase change material is 28°C PCM phase change material (Thermalcare PCM28°C, Shanghai Xinya New Material Technology Co., Ltd.).

[0107] Example 3

[0108] A lightweight, heat-insulating, high-strength building material, which is made of the following materials, calculated by mass percentage: 40.0wt% of silicate cement, 20wt% of lightweight aggregate, 26.5wt% of mineral fiber, 2.5wt% of modified nano-silicon dioxide, 5.0wt% of plant fiber reinforcing agent, and 6.0wt% of microcapsule phase change material;

[0109] The modified nano silicon dioxide is prepared by the following steps:

[0110] 1) Place the nano-silicon dioxide powder in an oven and dry it at 100-120°C for 12-24 hours to remove moisture and impurities adsorbed on the surface;

[0111] 2) dispersing the dried nano-silicon dioxide powder in anhydrous ethanol, and forming a uniform dispersion by ultrasonic treatment or high-speed stirring, wherein the content of the nano-silicon dioxide powder is 15wt%;

[0112] 3) mixing sodium lauryl sulfate and alumina powder with propylene glycol to form a modified solution, wherein the content of sodium lauryl sulfate is 7.5wt% and the content of alumina powder is 3.5wt%;

[0113] 4) slowly adding the above modifier solution to the nano-silicon dioxide dispersion at a volume ratio of 1:8; while maintaining stirring, so that the modifier is evenly covered on the surface of the nano-silicon dioxide by adsorption or coating;

[0114] 5) removing excess solvent and unabsorbed modifier by centrifugation, filtration or evaporation, and obtaining modified nano-silicon dioxide powder with a water content of less than 8 wt % after drying.

[0115] The plant fiber reinforcing agent includes bamboo fiber and flax fiber and is prepared by the following steps:

[0116] 1) Pretreatment: The bamboo fiber and flax fiber are pretreated separately, including washing, drying, and bleaching steps to remove surface impurities and grease, and the fibers are crushed into fragments less than 5 mm in length;

[0117] 2) Mixing: In a mixer, 10 parts of bamboo fiber, 4.5 parts of flax fiber and 7.5 parts of polyvinyl chloride powder are uniformly mixed by weight;

[0118] 3) Extrusion: The mixed materials are fed into a twin-screw extruder for extrusion, with the feeding zone at 50-60°C, the preheating zone at 100-110°C, the melting zone at 150-170°C, and the mixing zone at 175-185°C;

[0119] 4) Cooling and grinding: Cooling and grinding after extrusion, passing through a 50-mesh sieve to obtain the plant fiber reinforcing agent.

[0120] The method for preparing the above-mentioned lightweight thermal insulation high-strength building material is characterized by comprising the following steps:

[0121] S1 Mixing stage: Mix the silicate cement, lightweight aggregate, mineral fiber and modified nano-silicon dioxide in proportion to ensure that each component is fully dispersed;

[0122] S2 Pre-wetting treatment: Add appropriate amount of water to the plant fiber reinforcement for pre-wetting treatment to improve its dispersibility and binding force in the mixture;

[0123] S3 stirring and molding: adding the microcapsule phase change material and the pre-wetted plant fiber to the mixture obtained in step S1, adding an appropriate amount of water to adjust to a suitable workability, stirring mechanically until uniform, and molding using a mold;

[0124] S4 Curing and solidification: The formed materials are cured for 7-10 days under standard curing conditions at a temperature of 20±2℃ and a relative humidity of ≥90% to allow the cement to fully hydrate and harden, while the microcapsule phase change material is evenly distributed and fixed inside the material;

[0125] S5 post-processing: According to the needs, the finished product is cut, polished and processed to finally obtain lightweight, thermal insulation and high-strength building materials.

[0126] In S2, the mass ratio of the plant fiber reinforcing agent to water is 1:1.5; in S3, the mass ratio of the building material to water is 1:0.3.

[0127] The microcapsule phase change material is 28°C PCM phase change material (Thermalcare PCM28°C, Shanghai Xinya New Material Technology Co., Ltd.).

[0128] Comparative Example 1

[0129] A lightweight, heat-insulating, high-strength building material, which is made of the following materials, calculated by mass percentage: 35.0wt% of silicate cement, 25.0wt% of lightweight aggregate, 29wt% of mineral fiber, 2.0wt% of nano-silicon dioxide, 4.0wt% of plant fiber reinforcing agent, and 5.0wt% of microcapsule phase change material;

[0130] Compared with Example 2, the nano silicon dioxide is not modified, and the rest is the same.

[0131] Comparative Example 2

[0132] A lightweight, heat-insulating, high-strength building material, which is made of the following materials, calculated by mass percentage: 39.0wt% of silicate cement, 25.0wt% of lightweight aggregate, 29wt% of mineral fiber, 2.0wt% of modified nano-silicon dioxide, and 5.0wt% of microcapsule phase change material;

[0133] Compared with Example 2, no plant fiber reinforcing agent is contained, and a reduced amount is added to the silicate cement, and the rest is the same.

[0134] Comparative Example 3

[0135] A lightweight, heat-insulating, high-strength building material, which is made of the following materials, calculated by mass percentage: 40.0wt% of silicate cement, 25.0wt% of lightweight aggregate, 29wt% of mineral fiber, 2.0wt% of modified nano-silicon dioxide, and 4.0wt% of plant fiber reinforcing agent;

[0136] Compared with Example 2, no microcapsule phase change material is contained, and the reduced amount is added to the silicate cement, and the rest is the same.

[0137] Comparative Example 4

[0138] A light-weight heat-insulating high-strength building material is made of the following materials, calculated by mass percentage: 44.0wt% of silicate cement, 25.0wt% of lightweight aggregate, 29wt% of mineral fiber, and 2.0wt% of nano silicon dioxide.

[0139] Compared with Example 2, the nano silicon dioxide is not modified, does not contain plant fiber reinforcement and microcapsule phase change material, and the reduced amount is added to the silicate cement, and the rest is the same.

[0140] Comparative Example 5

[0141] Common thermal insulation building materials available on the market (main components: silicate cement and lightweight aggregate)

[0142] Test Example 1

[0143] Compressive strength and thermal insulation capacity were used to test the mechanical strength and other properties of Examples 1-3 and Comparative Examples 1-4. 100×100×100mm specimens were prepared according to GB / T5486-2008 "Test Methods for Inorganic Rigid Thermal Insulation Products" and mechanical strength tests were performed. The density was also tested. The results are shown in Tables 1 and Figure 1-3 .

[0144] Table 1 Mechanical properties test

[0145]

[0146] From the data in Table 1, it can be seen that the building materials prepared by Examples 1-3 of the present invention have excellent compressive strength and flexural strength. From the comparison between Example 2 and Comparative Examples 1-4, it can be seen that the building materials added with modified nano-silicon dioxide and plant fiber reinforcement are much stronger than the building materials without the above raw materials, and adding a small amount of microcapsule phase change material will not significantly affect the mechanical strength of the above materials. Compared with existing building materials, our building materials have obvious light weight characteristics.

[0147] Test Example 2

[0148] The thermal insulation properties of building materials were determined using the following method.

[0149] The building materials of Examples 1-3 and Comparative Examples 1-5 were made into plates with a side length of 1m and a thickness of 3cm. Six plates were combined to form a closed hollow square, and a temperature measuring device was installed in advance. The hollow square was placed in a room at a room temperature of 25°C for a long time. When the temperature was 25°C, the square was transferred to an environment simulating 50°C in the summer sun. The temperature was measured every 10min, 30min, 60min, 2h, 4h, and 8h through an external terminal. The results are shown in Table 2 and Figure 4 .

[0150] Table 2 Thermal insulation performance test

[0151]

[0152]

[0153] It can be seen from the data in Table 2 that the building materials prepared in Examples 1-3 of the present invention have good thermal insulation performance. Compared with the data in Comparative Documents 1-5, it can be seen that after adding microcapsule phase change materials and modified nano-silica, the thermal insulation performance of the building materials is greatly improved, and good mechanical strength can be maintained, which is very suitable for use in the construction of environmentally friendly and heat-insulating buildings.

[0154] It can be seen from the above embodiments and test examples that the present invention discloses a new type of building material, which can achieve lightweight, high-efficiency thermal insulation, and sufficient strength, and at the same time has a simple preparation process, low cost, and is environmentally friendly and pollution-free.

[0155] The above are limited to several preferred embodiments of the present invention, and the description is relatively specific and detailed, but it cannot be understood as limiting the scope of the present invention. It should be pointed out that for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention.

Claims

1. A lightweight, heat-insulating, high-strength building material, characterized in that: The main components are silicate cement, lightweight aggregate and mineral fiber, and the additives are modified nano silicon dioxide, plant fiber reinforcement and microcapsule phase change material. The added amount of the modified nano silicon dioxide is 1.5-2.5wt%, the added amount of the plant fiber reinforcement is 3-5wt%, and the added amount of the microcapsule phase change material is 4-6wt%.

2. A lightweight, heat-insulating, high-strength building material according to claim 1, characterized in that: The modified nano silicon dioxide is prepared by the following steps: 1) Place the nano-silicon dioxide powder in an oven and dry it at 100-120°C for 12-24 hours to remove moisture and impurities adsorbed on the surface; 2) dispersing the dried nano-silicon dioxide powder in anhydrous ethanol, and forming a uniform dispersion by ultrasonic treatment or high-speed stirring, wherein the content of the nano-silicon dioxide powder is 10-20wt%; 3) mixing sodium lauryl sulfate and alumina powder with propylene glycol to form a modified solution, wherein the content of sodium lauryl sulfate is 5-10wt%, and the content of alumina powder is 2-5wt%; 4) slowly adding the above modifier solution to the nano-silicon dioxide dispersion at a volume ratio of 1:5-10; while keeping stirring, so that the modifier is evenly covered on the surface of the nano-silicon dioxide by adsorption or coating; 5) removing excess solvent and unabsorbed modifier by centrifugation, filtration or evaporation, and obtaining modified nano-silicon dioxide powder with a water content of less than 8 wt % after drying.

3. A lightweight, heat-insulating, high-strength building material according to claim 1, characterized in that: The plant fiber reinforcing agent includes bamboo fiber and flax fiber and is prepared by the following steps: 1) Pretreatment: The bamboo fiber and flax fiber are pretreated separately, including washing, drying, and bleaching steps to remove surface impurities and grease, and the fibers are crushed into fragments less than 5 mm in length; 2) Mixing: In a mixer, 10 parts of bamboo fiber, 3-6 parts of flax fiber and 5-10 parts of polyvinyl chloride powder are uniformly mixed by weight; 3) Extrusion: The mixed materials are fed into a twin-screw extruder for extrusion, with the feeding zone at 50-60°C, the preheating zone at 100-110°C, the melting zone at 150-170°C, and the mixing zone at 175-185°C; 4) Cooling and grinding: Cooling and grinding after extrusion, passing through a 50-mesh sieve to obtain the plant fiber reinforcing agent.

4. A lightweight, heat-insulating, high-strength building material according to claim 1, characterized in that: The microcapsule phase change material is a microcapsule phase change material that changes phase at 28-45°C.

5. A lightweight, heat-insulating, high-strength building material according to claim 1, characterized in that: Calculated by mass percentage, it is made of the following materials: 30-40.0wt% of silicate cement, 20-30.0wt% of lightweight aggregate, 25-35wt% of mineral fiber, 1.5-2.5wt% of modified nano silicon dioxide, 3.0-5.0wt% of plant fiber reinforcement, and 4.0-6.0wt% of microcapsule phase change material.

6. A lightweight, heat-insulating, high-strength building material according to claim 5, characterized in that: Calculated by mass percentage, it is made of the following materials: 35.0wt% of silicate cement, 25.0wt% of lightweight aggregate, 29wt% of mineral fiber, 2.0wt% of modified nano-silicon dioxide, 4.0wt% of plant fiber reinforcement, and 5.0wt% of microcapsule phase change material.

7. Use of the lightweight, thermal insulation, high-strength building material as described in any one of claims 1 to 6 in the construction of environmentally friendly thermal insulation buildings.

8. The method for preparing a lightweight, heat-insulating, high-strength building material according to any one of claims 1 to 6, characterized in that: The following steps are involved: S1 Mixing stage: Mix the silicate cement, lightweight aggregate, mineral fiber and modified nano-silicon dioxide in proportion to ensure that each component is fully dispersed; S2 Pre-wetting treatment: Add appropriate amount of water to the plant fiber reinforcement for pre-wetting treatment to improve its dispersibility and binding force in the mixture; S3 stirring and molding: adding the microcapsule phase change material and the pre-wetted plant fiber to the mixture obtained in step S1, adding an appropriate amount of water to adjust to a suitable workability, stirring mechanically until uniform, and molding using a mold; S4 Curing and solidification: The formed materials are cured for 7-10 days under standard curing conditions at a temperature of 20±2℃ and a relative humidity of ≥90% to allow the cement to fully hydrate and harden, while the microcapsule phase change material is evenly distributed and fixed inside the material; S5 post-processing: According to the needs, the finished product is cut, polished and processed to finally obtain lightweight, thermal insulation and high-strength building materials.

9. The preparation method according to claim 8, characterized in that: In S2, the mass ratio of the plant fiber reinforcing agent to water is 1:1-2; in S3, the mass ratio of the building material to water is 1:0.2-0.4.